Growth Responses of Peppermint Plant (Mentha arvensis L.) to Several Sources of Natural Plant Growth Regulators - Nugraha, Andronicus Christian; Sukarjo, Entang Inoriah; Supanjani; Widodo (Akta Agrosia, 2025)
Indonesia, endowed with diverse medicinal plants, is exploring the commercial cultivation of peppermint plants (Mentha arvensis L.) to meet increasing demand for peppermint oil. This study investigated the effects of various natural plant growth regulators (PGRs) on peppermint plant growth and yield. Conducted in Bengkulu City from December 2020 to March 2021, the study used a Completely Randomized Design with 9 treatments of natural plant growth regulators and 3 replications. Results indicated that natural PGRs, including extracts from mung bean sprout filtrate, corn, shallots, and young coconut water, influenced leaf and tiller growth but showed no significant effects on plant height, number of branch shoots, stem segments, stolon, roots, leaf size, or essential oil aroma concentration. The combination of mung bean sprout filtrate and shallot filtrate yielded the greatest number of leaves. The findings suggest that while natural PGRs can enhance specific growth parameters, their overall impact on peppermint plant development may be limited by optimal soil conditions and nutrient availability. Keywords: leaf growth, mung bean sprouts, natural PGRs, peppermint, shallot extracts